Age Differences in Emotion Regulation Choice: Older Adults Use Distraction Less Than Younger Adults in High-Intensity Positive Contexts. (24th March 2016) - Martins, Bruna; Sheppes, Gal; Gross, James J; Mather, Mara
Abstract: Objectives: Previous research demonstrates that younger and older adults prefer distraction over engagement (reappraisal) when regulating high-intensity negative emotion. Older adults also demonstrate a greater bias for positive over negative information in attention and memory compared with younger adults. In this study, we investigated whether emotion regulation choice preferences may differ as a function of stimulus valence with age. Method: The effect of stimulus intensity on negative and positive emotion regulation strategy preferences was investigated in younger and older men. Participants indicated whether they favored distraction or reappraisal to attenuate emotional reactions to negative and positive images that varied in intensity. Results: Men in both age-groups preferred distraction over reappraisal when regulating high-intensity emotion. As no age-related strategic differences were found in negative emotion regulation preferences, older men chose to distract less from high-intensity positive images than did younger men. Discussion: Older men demonstrated greater engagement with highly positive emotional contexts than did younger men. Thus, age differences in emotion regulation goals when faced with intense emotional stimuli depend on the valence of the emotional stimuli.